Passivating Defects at the Bottom Interface of Perovskite by Ethylammonium to Improve the Performance of Perovskite Solar Cells. Issue 47 (13th October 2022) - Ren, Jiahao; Liu, Tanghao; He, Bingchen; Wu, Guangbao; Gu, Hao; Wang, Bingzhe; Li, Jielei; Mao, Yulin; Chen, Shi; Xing, Guichuan
Abstract: The interface of perovskite solar cells (PSCs) plays a significant role in influencing their performance, yet there is still scarce research focusing on their difficult‐to‐expose bottom interfaces. Herein, ethylammonium bromide (EABr) is introduced into the bottom interface and its passivation effects are studied directly. First, EABr can improve substrate wettability, which is beneficial for the perovskite‐film deposition. By lifting off the perovskite film spontaneously from the substrate, it is found that EABr can significantly reduce the amount of unreacted PbI2 at the bottom interface. These PbI2 crystals have been recently identified as a major defect source and degradation site for perovskite film. Meanwhile, EABr also lifts the valence band maximum at the bottom side of perovskite from ‐5.38 to ‐5.09 eV, facilitating better hole transfer. Such a improvement is also verified by the study of charge carrier dynamics. Through introducing EABr, all photovoltaic parameters of the inverted PSCs are improved, and their power conversion efficiency (PCE) increases from 20.41% to 21.06%. The study highlights the importance of direct characterization of the bottom interface for a better passivation effect. Abstract : An organic ammonium ion, ethylammonium (EA), is introduced to passivate defects caused by PbI2 residue at the bottom of the perovskite film. EA also contributes to increasing crystallization quality and energy‐level alignment at the interface. These changes are directly demonstrated by exposing the bottom interface. All photovoltaic parameters of perovskite solar cells are improved by introducing EA.